Pemanfaatan Limbah Sisik Ikan Nila dan Ikan Kakap Merah sebagai Kitosan - Risnita Tri Utami; Wica Elvina; Dedi Pardiansyah; Yulfiperius Yulfiperius (Universitas Batangahari Jambi, 2023)
Fish scales are leftover fishery products that are not utilized optimally. Fish scales contain chemical compounds such as organic protein, namely chitin, which is a derivative of chitosan. Chitosan can be used in various sectors such as the food industry, health, agricultural and cosmetics. This study aims to extract chitosan from the scales of farmed and marine fish, as well as to determine the ratio of the yield of chitosan to types of marine fish and cultivated fish. This research was conducted from July to August 2023. The fish scale samples used were tilapia (cultivated fish) and snapper (sea-caught fish) obtained from the Traditional Market and Fish Auction Place in Bengkulu City. The process of making chitosan is carried out in the Laboratory of the Faculty of Agriculture, Prof. Dr. Hazairin, SH University. The process of extracting chitosan from fish scales goes through three stages, namely deproteination, demineralization and deacetylation. The results showed that the water, ash and protein content of fish scales were different, namely tilapia (19.05%; 20.15%; 53.01%) and snapper. (10.78%; 43.54%; 28.49). Results of Tilapia Chitosan. (13.22%) and snapper (7.74%). Several chitosan characteristics such as color, shape and odor meet commercial chitosan standards.